Evolution of Julian Haynes Steward’s Concept of Cultural Ecology - Sadowski, Ryszard F. (Studia Ecologiae et Bioethicae, 2007)
Julian H. Steward is the author of anthropological approach called cultural ecology. Steward had been working on the concept for about forty years and used that approach in both his theoretical and field works, the version of cultural ecology presented in his most famous work Theory of Culture Change (1955) is significantly different than the form of the approach published in 1968. The goal of this essay is to present evolution in Steward’s understanding of cultural ecology, and to show the differences between the two main versions of the approach, the main difference between them is the disaperence of cultural core and three procedures - ideas which were the basis of the earlier form of cultural ecology. Changes in Steward’s approach caused problems for his other concept, especially for multilinear evolution of culture and the concept of types of culture.